2011
DOI: 10.5194/acp-11-12959-2011
|View full text |Cite
|
Sign up to set email alerts
|

Secondary new particle formation in Northern Finland Pallas site between the years 2000 and 2010

Abstract: Abstract. Secondary new particle formation affects atmospheric aerosol and cloud droplet numbers and thereby, the aerosol effects on climate. In this paper, the frequency of nucleation events and the associated particle formation and growth rates, along with their seasonal variation, was analysed based on over ten years of aerosol measurements conducted at the Pallas GAW station in northern Finland. The long-term measurements also allowed a detailed examination of factors possibly favouring or suppressing part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
115
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(140 citation statements)
references
References 68 publications
24
115
1
Order By: Relevance
“…October. The multi-year annual average of SSA at BRW was found to be 0.960 (see Table 2), which agrees with the 20 SSA averages of 0.96 presented for BRW data from 1988-1993 in Bodhaine (1995) and 1997-2000in Delene and Ogren (2002. PAL has higher SSA values in the summer and lower SSA values in the winter.…”
supporting
confidence: 74%
“…October. The multi-year annual average of SSA at BRW was found to be 0.960 (see Table 2), which agrees with the 20 SSA averages of 0.96 presented for BRW data from 1988-1993 in Bodhaine (1995) and 1997-2000in Delene and Ogren (2002. PAL has higher SSA values in the summer and lower SSA values in the winter.…”
supporting
confidence: 74%
“…Other contributing factors likely include long-range transport of anthropogenic aerosol from Europe as well as biogenic emissions Tunved et al, 2006). In addition, at PAL, there is increased contribution from continental air masses during the summer, which contribute to the higher scattering values (Aalto et al, 2002;Asmi et al, 2011). Figure 4 shows monthly median values of the aerosol light absorption coefficient (σ ap ) from corrected Aethalometer data at all six Arctic sites, as well as boxplots of absorption coefficients for all months.…”
Section: Spatiotemporal Variability Of Aerosol Optical Properties In mentioning
confidence: 99%
“…PAL is located at the lowest latitude of all the sites in the study and is the closest in proximity to the European continent. Although the site itself is located on top of a fell above the tree line, the station is surrounded by a forest and thus affected by nearby biogenic emissions during the summer active vegetation season (Tunved et al, 2006;Lihavainen et al, 2009;Asmi et al, 2011). SUM is the highest in elevation of all the sites and measures free-tropospheric air much of the year.…”
Section: Spatiotemporal Variability Of Aerosol Optical Properties In mentioning
confidence: 99%
“…A similar seasonal behaviour of GR has been observed earlier in Värriö (Dal Maso et al, 2007), but in Pallas only summer maximum is seen . The earlier onset of nucleation during spring has not been observed earlier in northern Finland (Vehkamäki et al, 2004;Asmi et al, 2011). Vehkamäki et al (2004) used the time when elevated concentrations of 8 nm particles were first observed, as the event start time, which shifts the spring event start times later since the growth rates are at their minimum in spring.…”
Section: General Characteristics Of New Particle Formation Eventsmentioning
confidence: 99%